2018
DOI: 10.1142/s2377740018500070
|View full text |Cite
|
Sign up to set email alerts
|

More Guns, Less Butter?: China-U.S. Arms Race Behind Southeast Asia’s Economic Boom

Abstract: Economic growth and arms race are interesting phenomena in Southeast Asia. Contrary to the view of a majority of scholars that arms race has generally negative impact on economic growth, this article argues that the arms race between China and the United States in the South China Sea helps to create a balance of power, which reinforces regional political stability and further drives economic growth. Thus, in an indirect way, the arms race aids economic growth in Southeast Asia. Elaborating on a discourse that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…Understanding China's tendency to prioritize economic interest over the cost of military clash (Mearsheimer, 2001) and without this determining role of Indonesia, China would depend solely on Indonesia's strategic diplomatic maneuver on securing regional stability. Indonesia's mediatory role becomes even more critical because security alliances among ASEAN members are divided between US allies (Thailand, Singapore and the Philippines) and China's (Cambodia, Laos and Myanmar), while Indonesia is a declared neutral (Pramono, 2018).…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding China's tendency to prioritize economic interest over the cost of military clash (Mearsheimer, 2001) and without this determining role of Indonesia, China would depend solely on Indonesia's strategic diplomatic maneuver on securing regional stability. Indonesia's mediatory role becomes even more critical because security alliances among ASEAN members are divided between US allies (Thailand, Singapore and the Philippines) and China's (Cambodia, Laos and Myanmar), while Indonesia is a declared neutral (Pramono, 2018).…”
Section: Results and Analysismentioning
confidence: 99%
“…Current growth in the region is provoked largely by China's investment and trade relations with countries in the region, however looming threat of China's growing military prominence that might jeopardize these countries remain. It is noteworthy that China -US rivalries, in turn, have created balance of power in the region that produces stability for economic growth (Pramono, 2018). In such situation, however, economic cooperation is challenging, yet Indonesia's role enables regional structure that facilitates it.…”
Section: Results and Analysismentioning
confidence: 99%
“…Second, studies found positive effects of military expenditure on the economy, among which (Pramono, 2018) wrote "the arms race between China and the United States in the South China Sea has become a process of regional power balance, which strengthens political stability and makes the region a dynamic engine of economic growth" (Pramono, 2018). Third, those who assume there is no relationship between the 2 variables.…”
Section: Literature Reviewmentioning
confidence: 99%